2015
DOI: 10.1038/sc.2015.119
|View full text |Cite
|
Sign up to set email alerts
|

A telephone-based version of the spinal cord injury–secondary conditions scale: a reliability and validity study

Abstract: Objective: The objective of this study was to determine the inter-rater reliability and validity of using a telephone-based version of the spinal cord injury-secondary conditions scale (SCI-SCS). Trial design: A psychometric study was conducted. Setting: The study was conducted in Royal North Shore Hospital, Sydney, Australia. Participants: Forty people with a complete or an incomplete spinal cord injury. Methods: Inter-rater reliability was tested by comparing the telephone-based version of the SCI-SCS admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Future versions of the SCI Secondary Conditions Scale need to clarify this distinction in the instructional text. 13 The responses to the participation items of the WHODAS indicated limited community engagement and other areas of concern. For example, 70% of participants who were wheelchair-dependent indicated that their SCI had created 'severe' family problems (n = 117/168) and a drain on their finances (n = 125/168).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future versions of the SCI Secondary Conditions Scale need to clarify this distinction in the instructional text. 13 The responses to the participation items of the WHODAS indicated limited community engagement and other areas of concern. For example, 70% of participants who were wheelchair-dependent indicated that their SCI had created 'severe' family problems (n = 117/168) and a drain on their finances (n = 125/168).…”
Section: Discussionmentioning
confidence: 99%
“…The telephone version of this scale has recently been validated. 13 The list of complications includes those related to pressure ulcers, bladder and bowel incontinence, pain, poor blood pressure control, contractures and spasm. Responses to each item are tallied.…”
Section: Outcomementioning
confidence: 99%
“…Data about secondary conditions were collected using the SCI-SCS. This is a standardised and validated 16-item questionnaire about complications such as pressure ulcers, respiratory problems, urinary and bladder incontinence, sexual dysfunction, autonomic dysreflexia, postural hypotension, spasticity, contractures and pain [16,17]. Participants were asked to rate the 16 items according to their experiences over the last three months on a 4-point scale (0-3) where a score of zero reflects "Not experienced in the last 3 months or not a significant problem" and a score of four reflects "Severe or chronic problem".…”
Section: The Spinal Cord Injuries Secondary Conditions Scale (Sci-scs)mentioning
confidence: 99%
“…The details of each secondary outcome are as follows: The burden of complications will be measured using the SCI Secondary Conditions Scale (SCI-SCS). 36 37 This is a 16-item scale. Each item is scored from 0 (did not experience the complication in the last 3 months) to 3 (significant or chronic problem over the past 3 months).…”
Section: Methods and Analysismentioning
confidence: 99%